Break Even Point Analysis To Increase The Sales Level Of Rengginan Special Cap Bawang In Pringsurat District Temanggung District - Myra Heltyani; Sri Martono (LPPM Universitas An Nuur, 2021)
Background: This study aims to determine the amount of profit earned, entrepreneurs must first know the level of Break Even Point (BEP) that is achieved, namely a situation where the company does not experience losses or profits. Methods: The type of research used in this research is descriptive research with a quantitative approach, the data source used is secondary data with the technique of collecting financial data from Rengginan Istimewa Cap Bawang in Pringsurat District, Magelang Regency. Results: From the calculation above, the number of goods sold for the May 2021 period so that the Rengginan Cap Bawang home industry reaches the Break Even Point is 19.46 units or when making sales of Rp. 388,568.00. If it exceeds the Break Even Point, it means a profit, but if it is less than the Break Even Point, it means a loss. Conclusion: Taking into account the results of the break even point analysis as a tool in planning sales in order to achieve the desired profit, it is better that the level or sales volume that must be achieved by the home industry of Rengginan Istimewa Cap Bawang should not fall from the results of the Break Even Point